Development & Characterization of Alginate/Graphene Oxide Fibers with Improved Electrical Conductivity (Journal of Fiber Bioengineering and Informatics, 2018)
Graphene has demonstrated extraordinary electrical, optical, thermal and mechanical properties. In last\rdecade, a lot of research has been done to improve fabrication and solution processing of graphene to\rgraphene oxide and reduced graphene oxide. Graphene oxide contains more number of oxygen containing\rfunctional groups which increase interlayer distance and make its dispersion easy in aqueous solutions.\rThese advances in graphene have further improved its properties including tensile strength, elastic\rmodulus, low resistance, carrier mobility and stability against higher temperatures and chemicals.\rAlginate is obtained from brown seaweeds and has potential applications in treatment of wounds and cell\rdifferentiation due to its non-toxicity, biodegradability and biocompatibility. It is a hydrophilic natural\rpolysaccharide and provides moist and ideal environment for wound healing and cell growth. However,\rAlginate fibers still also display some unsatisfactory properties, such as low mechanical strength and\relectrical conductivity. Combining the intriguing properties of graphene and alginate, we develop smart\rcomposite fibers with suitable conductivity and mechanical strength which can be processed to nonwoven\rwound dressings and can be used as biosensors for medical applications. Sodium alginate/Graphene oxide\rfibers were fabricated by using wet spinning setup. The developed sodium alginate/graphene oxide fibers\rwere further thermally and chemically reduced to improve conductivity. Their structure and properties\rwere characterized by conductivity measurements, fiber strength testing, absorption behaviors, FTIR\r(Fourier transform infrared spectroscopy) and SEM (scanning electron microscope). The addition of\rgraphene oxide improves the strength of sodium alginate/graphene oxide fibers due to high compatibility\rand even distribution of graphene oxide fillers in alginate matrix. Thermal and chemical reduction\rmethods increase the conductivity of sodium alginate/graphene oxide fibers due to removal of oxygen\rcontaining groups. Chemical reduction method seems to have greater effect in improving the conductive\rproperties of sodium alginate/graphene oxide fibers. These fibers also have good ability to absorb fluid\rand forms hydrogel to keep appropriate moist environment for wound healing which make them ideal\rmaterial to develop smart wound dressings.
Keywords: Alginate; Graphene; Conductivity; Fibers; Wet Spinning